The Arabidopsis DELAY OF GERMINATION 1 gene affects ABSCISIC ACID INSENSITIVE 5 (ABI5) expression and genetically interacts with ABI3 during Arabidopsis seed development. (5th February 2016) - Dekkers, Bas J.W.; He, Hanzi; Hanson, Johannes; Willems, Leo A.J.; Jamar, Diaan C.L.; Cueff, Gwendal; Rajjou, Loïc; Hilhorst, Henk W.M.; Bentsink, Leónie
Summary: The seed expressed gene DELAY OF GERMINATION ( DOG ) 1 is absolutely required for the induction of dormancy. Next to a non‐dormant phenotype, the dog1‐1 mutant is also characterized by a reduced seed longevity suggesting that DOG1 may affect additional seed processes as well. This aspect however, has been hardly studied and is poorly understood. To uncover additional roles of DOG1 in seeds we performed a detailed analysis of the dog1 mutant using both transcriptomics and metabolomics to investigate the molecular consequences of a dysfunctional DOG1 gene. Further, we used a genetic approach taking advantage of the weak aba insensitive (abi) 3‐1 allele as a sensitized genetic background in a cross with dog1‐1 . DOG1 affects the expression of hundreds of genes including LATE EMBRYOGENESIS ABUNDANT and HEAT SHOCK PROTEIN genes which are affected by DOG1 partly via control of ABI5 expression. Furthermore, the content of a subset of primary metabolites, which normally accumulate during seed maturation, was found to be affected in the dog1‐1 mutant. Surprisingly, the abi3‐1 dog1‐1 double mutant produced green seeds which are highly ABA insensitive, phenocopying severe abi3 mutants, indicating that dog1‐1 acts as an enhancer of the weak abi3‐1 allele and thus revealing a genetic interaction between both genes. Analysis of the dog1 and dog1 abi3 mutants revealed additional seed phenotypes and therefore we hypothesize that DOG1 function is not limited to dormancy but that it is required for multiple aspects of seed maturation, in part by interfering with ABA signalling components. Significance Statement: DELAY OF GERMINATION1 ( DOG1 ) is required for inducing seed dormancy but dog1 mutants also exhibit reduced seed longevity, due to an unknown mechanism, as DOG1 is a protein of unknown function. Here we show that DOG1 plays a more general role in seed maturation, in part by interfering with several ABA signalling components.